The importance of Turkish language society in the development of turkish language in Turkey (Journal of Oriental Studies, 2016)
The article considers the process of new turkish language formation during the Ataturk reforms and following period and the role of Turkish linguistic society in it. Also the article discusses the history of establishing the society, its goals, objectives, projects and activities. With analyzing aforementioned issues were defined main reasons of Turkish linguistic society’s succeeding in the language development.
Keywords: Turkish linguistic society; language reform; Turkish language; Ataturk